INNOVATIVE APPROACHES TO LEARNING THE GERMAN LANGUAGE - Saydaliyeva Mamura (Zeta Repository, 2023)
Innovative approaches used in the German language and its teaching process in the article, their implementation, quality changes in the values and needs of modern society in the modern conditions of education reform require corresponding changes in school education. One of the important criteria of the professional preparation of a pedagogue to work in modern conditions is his level of preparation for mastering innovative pedagogical educational technologies, the opinions and opinions of scientists are stated.